POSHAN’s abstract digest on maternal and child nutrition research – Issue 19 - Avula, Rasmi (International Food Policy Research Institute, 2017)
In this new year issue of Abstract Digest, we bring to you the much-awaited birth cohort MAL-ED study, two systematic reviews, as well as feature an article which mapped state-level disease burden and risk factors for the states in India, and several other interesting articles. In our non-peer reviewed section, we feature several papers from a book on ‘Nutritional Adequacy, Diversity and Choice Among Primary School Children: Policy and Practice in India.’